2014
DOI: 10.1089/pho.2013.3563
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-Controlled Investigation of Low-Level Laser Therapy to Treat Carpal Tunnel Syndrome

Abstract: This study has observed and documented the statistically significant short-term effects of LLLT on CTS patients in comparison with a placebo group. The results support this conclusion, especially if the LLLT is applied in the earlier stages of CTS, and with mild to moderate cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…One RCT by Lazovic was excluded because no available data can be pooled to calculate together. [ 29 ] No additional studies were obtained after the reference review. The search strategy ultimately identified 7 randomized clinical trials satisfying the predefined inclusion criteria; there were 270 wrists in the laser group and 261 wrists in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…One RCT by Lazovic was excluded because no available data can be pooled to calculate together. [ 29 ] No additional studies were obtained after the reference review. The search strategy ultimately identified 7 randomized clinical trials satisfying the predefined inclusion criteria; there were 270 wrists in the laser group and 261 wrists in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Conservative treatment is recommended in the mild and moderate stage of CTS245 and should involve splinting, steroid injections, oral steroids, and ultrasounds 5. However, the results of some research studies have showed the beneficial effect of photobiomodulation as well as nerve and tendon gliding exercises in nonoperative treatment 678910111213. It has been assumed that the analgesic, anti-inflammatory, and anti-edematous effects of the application of low-level laser and ultrasound might be caused by stimulation of biochemical and biophysical processes at the cellular and tissue level 1415.…”
Section: Introductionmentioning
confidence: 99%
“…There were significantly fewer cases with positive Tinel's sign (a clinical indicator of median nerve entrapment) in the active laser group, although a decrease in the presence of Tinel's sign was seen in both LLLT and control groups. There was also a significant decrease in the wrist to digit 2 median sensory nerve conduction velocity as compared with control [22]. This study indicates that LLLT may be beneficial for the treatment of both symptoms and nerve pathology in carpal tunnel syndrome.…”
Section: Carpal Tunnel Syndromementioning
confidence: 54%